Казки-“вандрівки” Івана Франка - Сабат, Г. (Слово і Час, 2008)
У статті аналізується характер нарації у формі подорожі в казках І.Франка. Наголошується, що герой-
мандрівник – надзвичайно поширений персонаж в естетичній системі романтизму – актуалізується у
творчості І.Франка, однак уже з неоромантичним забарвленням. Акцентується також увага на архетипі
Біди, який безпосередньо пов’язаний із трагічною темою творчості письменника – страдництва народу
в умовах колоніальної залежності. This article focuses upon the type of narration characteristic of Ivan Franko’s travel fairy tales. The
researcher shows, that the type of a travelling hero, which was extremely popular in the literature of
romanticism, was powerfully re-actualized in the works of I.Franko and thus became a part of the neoromantic
paradigm. A special attention is paid to the Misfortune archetype, which is directly linked to Franko’s
depainting of the people’s tragic sufferings under colonial circumstances. В статье анализируется характер нарации
в форме путешествия в сказках И.Франко.
Подчеркнуто, что герой-путешественник –
очень популярный персонаж в эстетической
системе романтизма – актуализируется в
творчестве И.Франко, правда, представлен
уже на неоромантическом уровне.
Акцентируется также внимание на архетипе
Беды, который непосредственно связан с
трагической темой творчества писателя –
страданий народа в условиях колониальной
зависимости.